2022
DOI: 10.1371/journal.pone.0275341
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin may be associated with duodenal eosinophils through the expression of PAR2 in early chronic pancreatitis and functional dyspepsia with pancreatic enzyme abnormalities

Abstract: Background Early chronic pancreatitis (ECP) has been reported to advance into chronic pancreatitis, it may be critical to differentiate the pathophysiology of ECP and functional dyspepsia (FD) in patients with pancreatic enzyme abnormalities (FD-P). This study aimed to clarify differences in the pathophysiology of ECP and FD-P and to determine whether duodenal inflammatory responses in the two diseases were associated with protease-activated receptor (PAR) 2, as the trypsin receptor. Methods Eighty patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Because PAR2 is ubiquitously expressed in gastrointestinal mucosal cells, smooth muscle cells, and neurons, activation of PAR2 induces a wide range of processes such as triggering intestinal secretion, modulating gastrointestinal motility, 40,41 participating in colonic inflammatory reactions and visceral hypersensitivity 42 . We have previously reported that PAR2 expression was localized in the duodenal epithelium and duodenal eosinophils in patients with FD with pancreatic enzyme abnormalities (FD‐P) 21 . We have also reported that PAR2 was localized in degranulated eosinophils in the duodenum of patients with FD‐P 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Because PAR2 is ubiquitously expressed in gastrointestinal mucosal cells, smooth muscle cells, and neurons, activation of PAR2 induces a wide range of processes such as triggering intestinal secretion, modulating gastrointestinal motility, 40,41 participating in colonic inflammatory reactions and visceral hypersensitivity 42 . We have previously reported that PAR2 expression was localized in the duodenal epithelium and duodenal eosinophils in patients with FD with pancreatic enzyme abnormalities (FD‐P) 21 . We have also reported that PAR2 was localized in degranulated eosinophils in the duodenum of patients with FD‐P 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms of patients with FD were estimated based on the Rome IV criteria. 19,20 At least one of the following clinical symptoms must be present in patients with FD: early satiation, bothersome postprandial fullness, epigastric pain, or epigastric burning. Postprandial distress syndrome and epigastric pain syndrome were diagnosed when symptoms persisted for at least 3 months, and the onset of symptoms was at least 6 months before the diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, FD symptoms, including epigastric pain, epigastric burning, postprandial fullness, and early satiety, as well as treatment satisfaction were assessed based on the Rome IV classification as follows: 0, none; 1, very mild; 2, mild; 3, moderate; 4, severe; and 5, very severe. 19,20 Clinical symptoms were also evaluated using the Gastrointestinal Symptom Rating Scale (GSRS). 21 In particular, we used the mean GSRS score and its 15 GI symptoms for the evaluation of dyspeptic symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations